Leadership in Peer Group Mentoring - Jonathan Kroll; Regina M. O’Neill (International Journal of Evidence Based Coaching and Mentoring, 2025)
In traditional one-to-one mentoring relationships, the mentor is typically perceived as the leader and the mentee serves as a follower. In peer group mentoring experiences, traditional notions of top-down leadership and hierarchical decision-making are purposefully avoided. In this study we wanted to explore how leadership manifested in peer mentoring groups. A narrative inquiry was utilized to capture the voices and experiences of twelve peer mentoring group participants. Our study found leadership was necessary to ensure coordination of administrative tasks as well as to facilitate healthy exchanges between group members.